Skopelos, Türkei. Surveyprojekt im byzantinisch-bulgarischen Grenzgebiet in Ostthrakien. Die Arbeiten der Jahre 2017 und 2018 - Fildhuth, Jesko (e-Forschungsberichte des DAI, 2019)
Skopelos is a heavily fortified byzantine hilltop settlement and bishopric located near the Strandzha Mountains (Yıldız Dağları) in eastern Thrace, close to the ancient border between the Byzantine Empire and the Bulgarian Khanate. The town was founded in the 8th century AD and occupied until the 14th century when it was abandoned after the Ottoman conquest. In addition, the site was connected to a network of numerous small castles, situated in the Strandzha Mountains. The site of Skopelos and four of the castles in the vicinity were studied during two field campaigns of a Survey Project.